Metastatic Jejunal Adenocarcinoma in the Hepatobiliary Limb Post-Liver Transplant: Diagnostic Challenges in a Patient with Roux-en-Y Gastric Bypass - Yash R. Shah; Carensa Cezar; Heena Khan; Sumant Inamdar; Mauricio Garcia Saenz De Sicilia; Matthew G. Deneke; Mary K. Rude (Gastrointestinal Disorders)
Background: The rise in bariatric surgeries, particularly Roux-en-Y gastric bypass (RYGB), has added complexity to diagnostic evaluations in post-transplant patients. Case Presentation: We present a rare case of metastatic jejunal adenocarcinoma in the biliopancreatic limb of a patient with a history of RYGB, diagnosed three months after simultaneous liver–kidney transplantation. Despite multiple advanced imaging modalities, the primary malignancy eluded detection during pre-transplant evaluation. The patient developed progressive anemia and persistent liver enzyme elevation, which led to a comprehensive diagnostic workup. After failed initial endoscopic and radiological attempts, a multifaceted approach combining PET-CT, targeted open liver biopsy, and repeat endoscopy via a G-tube site enabled the discovery of a 5 cm partially obstructing jejunal mass. Histopathological analysis confirmed moderately differentiated adenocarcinoma. Conclusions: This case underscores the challenges in diagnosing gastrointestinal malignancies in patients with altered anatomy, particularly following RYGB. It highlights the need for modified cancer screening protocols before organ transplantation, especially for those with complex post-surgical gastrointestinal anatomy, to prevent the development of metastatic disease post-transplant. Further research is warranted to refine screening strategies and improve early malignancy detection in this high-risk population.